Impacts of the Russian and Ukranian Conflict (2022- the Present) - Boudjnane, Adlane (My University, 2023)
This study explores the impact of the Russian-Ukrainian conflict, which began in February 2022, on the United States. Also, it delves into the economic, political, and security dimensions of this conflict and how they have shaped the United States of America’s behaviour on the global stage. Economically, it examines how fluctuations in international trade and energy markets affect everyday life in the United States of America. Politically, it highlights the nation's efforts to build alliances, garner international support, and impose sanctions on Russia to maintain global stability and influence. In terms of security, the study considers how strategic alliances and friendships worldwide contribute to safeguarding American interests. Ultimately, this research illuminates the profound impact of the ongoing conflict on the United States of America’s domestic policies and its role in the world.
Keywords: USA; EU; Russia; Ukraine; Putin; Zelensky